#### Answer

33x$^2$

#### Work Step by Step

Simplify the expression by combing like terms.
34x$^2$-x$^2$=(34-1)x$^2$=33x$^2$

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

33x$^2$

Simplify the expression by combing like terms.
34x$^2$-x$^2$=(34-1)x$^2$=33x$^2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.